Analisis Budaya Sekolah Berbasis Hak Asasi Manusia Melalui Hubungan Kelas: Tinjauan Pustaka Bab Buku Charlotte Carter dan Audrey Osler - Hardiyansah, Yoga; Afriansyah, Ardi (FKIP, UNIVERSITAS ISLAM SYEKH-YUSUF TANGERANG, 2024)
Human rights represent the cornerstone of a just and inclusive society, ensuring that every individual is afforded dignity and respect. However, the realization of these rights often faces challenges due to differing perspectives, ethnicities, races, religions, and cultures within communities. Consequently, it becomes imperative to instill a strong emphasis on human rights within society, particularly within educational institutions. In addressing these challenges, schools play a pivotal role in promoting democratic values and multicultural understanding among students. Yet, merely claiming to uphold democratic principles without ensuring the rights and responsibilities of all students undermines the essence of true democracy. Research, such as the systematic literature review conducted by Charlotte Carter and Audrey Osler on human rights, identity, and conflict management in school cultures, underscores the necessity of integrating human rights principles into the fabric of school culture. Key aspects essential for the implementation of human rights in schools include democratic practices that ensure equal access and active participation for all, fostering inclusivity where diversity is not just acknowledged but celebrated, and establishing transparent school structures that are accountable to their stakeholders. These fundamental changes in school culture are imperative to create an environment where every individual feels valued and respected, ultimately contributing to a more harmonious and equitable society